Pelatihan Pengenalan dan Pengujian Content Creator di LSP IT di Jakarta Timur - Firdaus, Mohamad; Fatoni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2025)
The content creator profession is growing rapidly and plays an important role in today's digital ecosystem. However, there are still many individuals who pursue this profession who do not have officially recognised competency certification. Therefore, this community service activity was carried out with the aim of introducing the content creator profession formally, as well as providing education and training in preparation for the competency certification test through the Information Technology Professional Certification Institute (LSP) in the East Jakarta area. This activity was carried out in February 2025 by involving youth and the general public who have an interest in digital content creation. The implementation method includes counselling, technical training, and competency test simulations in accordance with the applicable certification scheme. The results of the activity showed an increase in participants' understanding of the structure and requirements in the content creator certification test, as well as an increase in participants' readiness to face the certification process. This activity encourages formal recognition of the content creator profession while contributing to improving the quality of human resources in the digital economy.